Strategic Antecedents and Consequents for the Performance of E-Business Companies - Elnivan Moreira de Souza; Paulo César de Sousa Batista (BBR: Brazilian Business Review)
This article aims to examine the influence of the strategic background and of the business model elements on its value proposition, and to investigate the relationship between the value proposition and the performance of e-business. The research is supported theoretically by the Technological, Organizational and Environmental framework (TOE), derived from the Diffusion of Innovation Theory (DIT), for the Strategic Background (IFINEDO, 2011), by the Business Model theory (OSTERWALDER; PIGNEUR; 2010; SOUZA; BATISTA, 2014) and by the business performance literature (RAMANUJAN; VENKATRAMAN, 1987). We tested the proposed model with a sample of 252 observations, using the structural equation modeling. The main results indicate a partial influence of the strategic background in the value proposition through the constructs management positioning, organizational readiness, relative advantage and pressure from stakeholders. Relating to the business model, the constructs of market segmentation, customer relationships, capabilities, partnerships and revenue model influence the value proposition, which in turn affects positively the performance of e-business companies.